Sistem Informasi Manajemen Aset Tetap Menggunakan Metode Waterfall - Garnish Ayu Andini Wijaya; Ali Ikhwan; Raissa Amanda Putri (STMIK Budi Darma, 2023)
PT. X is one of the 29 (twenty nine) oil palm plantations managed by PT. XY which is engaged in the agro-industry business. Assets are an important part of a company, so their management must also be appropriate. In managing the fixed assets contained in PT. X has been computerized using Microsoft Excel in the process of managing fixed asset data, but as a data processing tool Microsoft Excel has problems in presenting fixed asset reports which are quite time-consuming and inefficient, annual depreciation calculations must be inputted periodically, lots of fixed asset data in the form of transactions, monitoring, depreciation and procurement which are likely to be scattered and not well organized. The design of a web-based fixed asset management information system uses the waterfall method which has several stages, namely: system analysis, system design, program coding, program testing, system implementation and system maintenance. Testing this website is in the form of a black box test. The result of this design is a fixed asset management information system for PT. X web-based by using the straight line method (Straight Line method) on depreciation of fixed assets. Then the results of testing the menu on the website go well as it should so it is expected that the website can be useful for PT. X and employees who work at PT. X.